Late Gadolinium Enhancement Amount As an Independent Risk Factor for the Incidence of Adverse Cardiovascular Events in Patients with Stage C or D Heart Failure - Liu, Tong; Ma, Xiaohai; Liu, Wei; Ling, Shukuan; Zhao, Lei; Xu, Lei; Song, Deli; Liu, Jie; Sun, Zhonghua; Fan, Zhanming; Luo, Taiyang; Kang, Junping; et al. (Frontiers in Physiology, 2016)
Background: Myocardial fibrosis (MF) is a risk factor for poor prognosis in dilated cardiomyopathy (DCM). Late gadolinium enhancement (LGE) of the myocardium on cardiac magnetic resonance (CMR) represents MF. We examined whether the LGE amount increases the incidence of adverse cardiovascular events in patients with stage C or D heart failure (HF). Methods: Eighty-four consecutive patients with stage C or D HF, either ischemic or non-ischemic, were enrolled. Comprehensive clinical and CMR evaluations were performed. All patients were followed up for a composite endpoint of cardiovascular death, heart transplantation, and cardiac resynchronization therapy with defibrillator (CRT-D). Results: LGE was present in 79.7% of the end-stage HF patients. LGE distribution patterns were mid-wall, epi-myocardial, endo-myocardial, and the morphological patterns were patchy, transmural, and diffuse. During the average follow-up of 544 days, 13 (15.5%) patients had endpoint events: 7 patients cardiac death, 2 patients heart transplantation, and 4 patients underwent CRT-D implantation. On univariate analysis, LGE quantification on cardiac magnetic resonance, blood urine nitrogen, QRS duration on electrocardiogram, left ventricular end-diastolic diameter (LVEDD), and left ventricular end-diastolic volume (LVEDV) on CMR had the strongest associations with the composite endpoint events. However, on multivariate analysis for both Model I (after adjusting for age, sex, and body mass index) and Model II (after adjusting for age, sex, BMI, renal function, QRS duration, and atrial fibrillation on electrocardiogram, the etiology of HF, LVEF, CMR-LVEDD, and CMR-LVEDV), LGE amount was a significant risk factor for composite endpoint events (Model I 6SD HR 1.037, 95%CI 1.005–1.071, p = 0.022; Model II 6SD HR 1.045, 95%CI 1.001–1.084, p = 0.022). Conclusion: LGE amount from high-scale threshold on CMR increased the incidence of adverse cardiovascular events for patients in either stage C or D HF.